DUNIA HORIZONTAL DAN DUNIA VERTIKAL DALAM SUPER HILANG, SEGEROBAK SAJAK HAMID JABBAR SUATU TINJAUAN STRUKTURALISME SEMIOTIK - Thahar, Harris Effendi (Diksi, 2015)
This article aims at revealing expression of social protest as a horizontal world and religious expression as a vertical one in the anthology of poems Super Hilang by Hamid Jabbar. By means of a structural semiotic approach, it is revealed that the poems gathered in the anthology constitute poems which are heavy with expression of social protest and simultaneously heavy with religious expression. It indicates that they are poems expressing the horizontal world of the poet as a part of his society and the vertical world of the poet as a helpless being in the presence of God. Keywords: horizontal world, vertical world, anthology, poem, semiotic structuralism